An Atypical Presentation of Hemophagocytic Lymphohistiocytosis (HLH) Secondary to Occult Hodgkin Lymphoma - Justin Komisarof; Kevin McGann; Alissa Huston; Hani Katerji; Mary Anne Morgan (Case Reports in Hematology)
Hemophagocytic lymphohistiocytosis (HLH) is a rare and life-threatening syndrome of immune system dysregulation characterized by the phagocytosis of various cells by histiocytes in the bone marrow. HLH can present in one of the two ways: primary HLH, which is caused by mutations in genes essential to T and NK-cell function, and secondary HLH, typically caused by Epstein–Barr virus (EBV) infection or malignancy. Because of the rapid progression and high mortality of this disease, prompt diagnosis is essential to good outcomes. Here, we report the 2-month clinical course of a patient who presented with altered mental status and recurrent fever of unknown origin. Initially, he did not meet diagnostic criteria for HLH and had a negative bone marrow biopsy; however, he eventually progressed to full-blown HLH secondary to occult Hodgkin lymphoma. This case is unusual for the slow and smoldering course of the patient’s disease and highlights the importance of aggressively searching for potential malignancies to ensure the initiation of definitive therapy as soon as possible.